Selling and Sales Management - Jobber David; Lancaster Geoff (Ft Prentice Hall, 2006)
This excellent work is mandatory reading for all with academic or practical interests in the world of sales - which is about the whole marketing and management community. This influential book is an excellent contribution to the literature. Preface, Acknowledgements, One Sales Perspective, Development and Role of Selling in Marketing, Sales Strategies, Sales Environment, Consumer and Organizational Buyer Behavior, Sales Settings, International Selling, Law and Ethical Issues, Sales Technique, Sales Responsibilities and Preparation, Personal Selling Skills, Key Account Management, Relationship Selling, Direct Marketing, Internet and IT Applications in Selling and Sales Management, Sales Management, Recruitment and Selection, Motivation and Training, Organization and Compensation, Sales Control, Sales Forecasting and Budgeting, Salesforce Evaluation, Appendix: Examination Technique, Further Reading, Index.